Analysis Of The Role Of National Health Insurance Cadres In The Collectibility Of BPJS Health Contributions In Medan City - Yanti Parinduri, Ramadha; Sukristyanto, Agus; Novaria, Rachmawati (International Journal of Educational Research & Social Sciences, 2024)
This study discusses the role of JKN-KIS Cadres in the collectibility of BPJS Health contributions in Medan City. Based on the background of the problem, Medan City is experiencing a very large funding deficit in BPJS Health, so that financing of health facility and hospital funding claims will be hampered. Judging from several problems, the factors that cause the funding to swell are due to the large number of JKN-KIS participants who stop paying contributions so that expenses are not comparable to income. One of the methods used by BPJS Kesehatan Medan City based on BPJS Kesehatan Board of Directors Regulation No. 4 of 2017 concerning Guidelines for the Implementation of JKN-KIS Cadres is to recruit JKN-KIS Cadres as a collection and collection of participant contributions. So that with this Cadre network, it can increase income for BPJS Kesehatan. Therefore, to analyze the role of the JKN-KIS Cadres, the researcher used quantitative and qualitative or mixed research methods where the quantitative approach focuses on numbers and measurable data, the qualitative approach focuses on deepening the respondent's experience of the events they experienced. Data collection techniques use open questionnaires, interviews, observations and other supporting documents. Data analysis using Huberman and Miles analysis techniques, namely; reducing data, presenting data, and concluding data. Based on the results obtained, it shows that the role of JKN-KIS Cadres in the collectibility of BPJS Kesehatan contributions in Medan City has had a significant impact and has been implemented well as much as 33.06% even though there has been a reduction and the target achievement has not been achieved, but with the role of Cadres implemented in Medan City, it also has an impact in serving the community related to the dissemination of JKN information and BPJS Kesehatan social marketing. The things that are the lack of collectibility of contributions carried out by JKN-KIS Cadres are that Medan City has UHC so that people who are in arrears will feel lazy in making payment bills that have been in arrears.